Analysis of Deviant Behavior in Elementary School Children at SD Negeri Doplang 04 Adipala - Dhimas Pinasthika; Sriyanto Sriyanto (UM Purwokerto Press, 2025)
Deviant behavior among elementary school students has recently become increasingly prevalent, particularly in the form of negative deviations. Given the rise of negative deviant behavior in elementary schools, research on this issue is necessary. This study, conducted at SD Negeri Doplang 04 Adipala, aims to identify the influencing factors, the forms of negative deviant behavior, and the efforts made to prevent and address such behaviors among elementary school-aged children. This research employs a qualitative descriptive method with a case study design to provide an in-depth description of the findings. The results show that the factors influencing negative deviant behavior include habits, peer associations, environmental influences, lack of awareness of existing rules, rapid changes in norms, and unclear regulations, which can lead children to lose their sense of guidance and seek self-expression through deviant actions. Forms of negative deviant behavior at school include vandalizing school facilities, cheating, extorting money from peers, not doing homework, climbing over fences, leaving school without permission, neglecting cleaning duties, littering, and truancy. The follow-up efforts taken include restitution approaches, persuasive actions, positive reinforcement, and collaboration with parents.